Strategi Pembentukan Karakter Religius Santri Melalui Pembiasaan Sholat Tahajud Di Pondok Pesantren Kebon Dalem Desa Tanggungan Kecamatan Pucuk Kabupaten Lamongan - Arfiyanto, Agus Nanda; Habibah, Sulhatul (Fakultas Agama Islam, 2026)
Religious character education is the core of the Islamic education system, especially in Islamic boarding schools. However, the rapid flow of modernization and low spiritual awareness are evident in the behavior of students, such as starting to neglect sunnah worship, and being easily influenced by practical lifestyles. This condition is a serious challenge, including at the Kebon Dalem Islamic Boarding School in Tanggungan Village. To address this challenge, this Islamic boarding school implements several strategies through the habit of praying Tahajud as a means of forming the religious character of students. The objectives of this study are (1) to describe the strategies implemented (2) to identify supporting and inhibiting factors (3) to analyze the impact of the habit of praying Tahajud on the formation of religious character of students. This study uses a descriptive qualitative approach with observation, interview, and documentation techniques. The results of the study show that (1) The strategies implemented include role models, routine scheduling, supervision, personal motivation and emotional approaches, and evaluation (2) Supporting factors such as the active role of administrators, religious environment, and student awareness. While inhibiting factors include laziness, physical condition, lack of sleep patterns, and different backgrounds (3) The impact of religious character formation is seen in positive thinking patterns, good behavior, piety, istiqomah, patience, and sincerity in worship. So this finding confirms that the habit of praying Tahajud with the right strategy is able to form the religious character of students effectively and sustainably.